Effects of probiotics (cultured Lactobacillus subtilis/Streptococcus faecium) in the treatment of alcoholic hepatitis: randomized-controlled multicenter study. Issue 11 (November 2015) - Han, Sang Hak; Suk, Ki Tae; Kim, Dong Joon; Kim, Moon Young; Baik, Soon Koo; Kim, Young Don; Cheon, Gab Jin; Choi, Dae Hee; Ham, Young Lim; Shin, Dong Hoon; Kim, Eun Ji
Abstract : Background: Probiotics might reduce gut-derived microbial lipopolysaccharide (LPS) by restoring bowel flora in patients with alcoholic hepatitis (AH). We evaluated the therapeutic effects of probiotics in patients with AH. Patients and methods: Between September 2010 and April 2012, 117 patients (probiotics 60 and placebo 57) were prospectively randomized to receive the 7 days of cultured Lactobacillus subtilis/Streptococcus faecium (1500 mg/day) or placebo. All patients were hospitalized and were not permitted to consume alcohol for the 7 days of the study. Liver function test, proinflammatory cytokines, LPS, and colony-forming units by stool culture were examined and compared after therapy. Results: In both groups, the mean levels of aspartate aminotransferase/alanine aminotransferase, alkaline phosphatase, γ-glutamyl transpeptidase, bilirubin, and prothrombin time were significantly improved after 7 days of abstinence. In the probiotics group (baseline and after), albumin (3.5±0.7 and 3.7±0.6 g/dl, P =0.038) and tumor necrosis factor-α (121±244 and 71±123 pg/ml, P =0.047) showed differences. In addition, the number of colony-forming units of Escherichia coli was significantly reduced (435±287 and 168±210, P =0.002). In the placebo group, the level of LPS (1.7±2.8 and 2.0±2.7 EU/ml) was significantly increased. In the intergroup comparison, significant differences in the levels of tumor necrosis factor-α ( P =0.042) and LPS ( P =0.028) were observed between the groups. Conclusion: Immediate abstinence is the most important treatment for patients with AH. In addition, 7 days of oral supplementation with cultured L. subtilis/S. faecium was associated with restoration of bowel flora and improvement of LPS in patients with AH.